An Investigation of Consumer Participation and Co-Creation Value in Facebook - Chiu, Yu-Ting (2010)
With the rapid growth of virtual communities, more and more people rely on participating in virtual communities to communicate with others, exchange information or use entertainment functions. Many researchers have explored consumer behaviour in virtual communities; however, there is still a lack of research concerning consumers’ motivation factors in participating in the most popular virtual community, Facebook. Hence, the aim of the research is to investigate factors which influence consumers’ participation in Facebook and to explore the underlying value of Facebook. An online questionnaire survey was conducted to answer the research questions. Effective samples were collected from 268 respondents who have used Facebook. The results show that purposive value, interpersonal interconnectivity and interactive function have a significant influence on consumers’ participation in Facebook. Moreover, Facebook provides an efficient platform for both consumers and businesses to co-create value. The study gives academics new perspectives regarding consumer behaviour in Facebook. It also provides practitioners with a better understanding when conducting marketing strategies on Facebook. Finally, future research is recommended in the marketing area.